Taxonomy of the genus Iyengaria Borgesen (Phaeophycota) from coastal waters of Karachi, Pakistan - Aisha, K.; Shameel, M. (Альгология, 2015)
Globular, hollow and stellate thalli of the brown algal genus Iyengaria were collected from various coastal areas of Karachi and taxonomically investigated. This study revealed the presence of two species i.e. I. stellata (Børgesen) Børgesen and a new species, I. lobocylindrica Aisha et Shameel. The new species is characterized by the thin walled thallus, hollow projections, cortex not differentiated into inner and outer portion, absence of phaeophycotaen hairs, and thin walled plurilocular sporangia with rectangular locules. Its thalli are lobed in early stages but gradually become cylindrical.